Matrix metalloproteinase‐1 promoter ‐1607 bp 1G/2G polymorphism associated with increased risk of spinal tuberculosis in Southern Chinese Han population. Issue 6 (27th January 2017) - Zhou, Ying; Gao, Qile; He, Dan; Deng, Ang; Huang, Rongfu; Li, Yanbing; Tan, Chunyan; Guo, Chaofeng; Guo, Qiang; Wang, Longjie; Yang, Guanteng; Zhang, Hongqi
Abstract : Background: Spinal tuberculosis is the most common form of musculoskeletal tuberculosis. The expression of matrix metalloproteinase‐1 (MMP‐1) is increased in cells with Mycobacterium tuberculosis infection. MMP‐1 plays a curial role in extracellular matrix degradation during the progression of tuberculosis. Although the 1G/2G polymorphism in MMP‐1 ‐1607 influences its transcription, its role in spinal tuberculosis remains unknown. Methods: Healthy controls and patients with spinal tuberculosis of Han ethnicity were recruited between January 2010 and May 2016. The MMP‐1 ‐1607 1G/2G polymorphism was genotyped using the Sequenom mass Array polymorphism analysis system. Results: The genotypes of 1G/1G, 1G/2G, and 2G/2G were found in 13.7%, 53.6%, and 32.8% of patients, and 12.2%, 37.4%, and 50.4% of controls, respectively. The 1G/2G genotype were more common in cases than in controls ( P =2.05E‐04). The 1G allele showed an association with an increased risk for spinal tuberculosis when compared to 2G allele ( P =.004). 1G genotypes, having at least one 1G allele, were associated with the risk of developing spinal tuberculosis (1G/1G+1G/2G vs 2G/2G: OR=2.084, 95%CI=1.401‐3.100, P =2.65E‐04). Conclusion: 1G genotypes of the MMP‐1 ‐1607 may be associated with susceptibility to spinal tuberculosis in Southern Chinese Han population.